Evaluation of intermittent hemodialysis conducted off-site on patients with renal insufficiency admitted in the intensive care unit of a developing country - Simour, Aïcha; Dendane, Tarek; Abidi, Khalid; Belayachi, Jihane; Madani, Naoufel; Iraqi, Amina; Abouqal, Redouane; Zeggwagh, Amine A. (International Journal of Research in Medical Sciences, 2019)
Background: In most developing countries, the renal replacement therapy (RRT) in ICU is not performed locally. We designed this study to assess the intermittent hemodialysis (IHD) offsite intakes on survival in critically ill patients admitted with renal failure. Methods: We prospectively analyzed all patients admitted to medical ICU with Acute Renal Failure (AKF) or Chronic Renal Failure (CKF) from February 2011 to September 2013. Patients were divided into two groups: those that received IHD in Hemodialysis Unit (IHD+) and those who did not (IHD-). Every patient IHD+ was matched to a patient IHD - using propensity score. Results: 202 patients were included: 151 with ARF and 51 with CRF. 116 patients were matched (age: 48±18 years; 46F/70M; median serum creatinine: 51mg/l; IQR: 32-90 mg/l). The total number of dialysis sessions was 112 for 58 patients (1.8±1.4 session/patient). The median delay to initiate IHD was 5.5h (IQR: 2-8h) and median duration of transportation was 10 min (IQR: 10-15min) with 23.6% transportation incidents. Significant hypotension with tachycardia were reported during IHD. ICU mortality rate was the same in the both groups (58.6%). In multivariate analysis, CRF (RR=2.69; p=0.006), serum creatinine >50mg/l (RR=3.54; p=0.007) and requirement for vasopressors infusion (RR=1.8; p=0.041) were independent predictive factors for receiving IHD. Conclusions: Our study doesn’t show an improvement in survival in ICU patients who receive IHD offsite. The probability to require IHD offsite increases with CRF and the use of vasopressors.